Heavy Metal Characteristics of Soil and Leachate Resistivity Mapping of Malacca Landfll - Amir Detho, Amir Detho; Abdul Kadir, Aeslina; Zawani, Zuwairi Izwan (Springer, 2024)
Disposal of solid wastes through landfll becomes more expensive and has shortened the lifespan of the landfll as the generation of waste is increasing rapidly. In addition, the construction of new landflls becomes a constraint due to the lack of sufcient site, rising land prices, and increasing demands. Some factors such as the population growth, less sanitary landfll, and poor management of solid waste led to difculties in treating large amounts of leachate. Due to the leachate infltrating into the soil, it can pollute the groundwater and afect the nature that is located around the dumping site. In order to detect the movement of leachate in landfll and to determine the contamination area of leachate, the electrical resistivity method is more suitable to use in terms of cost and time required. The aim of this research is to determine the properties of heavy metal in soil, analyse electrical resistivity method using Schlumberger confguration, and determine and produce the subsurface profle of electrical resistivity mapping for leachate at Krubong landfll. The soil characteristics were determined using XRF From the result, the highest heavy metal concentration in a sample from Krubong landfll site is barium (Ba) followed by zirconium (Zr), and vanadium (V). The study was focused on the application of the geophysics method by electrical resistivity in survey work using a Terrameter SAS4000 imaging system to produce a subsurface profle of the Krubong landfll. Three spread lines were successfully installed and applied at the site to get the subsurface profle of the site. According to the resistivity result, there are some spots at the subsurface of the site that show the leachate plume. Therefore, the movement of leachate can be determined and will assist in the improvement of landfll management and treatment purposes.